A rare case of blast injury of the chest and spine on the background of a congenital malformation in the form of a complete mirror image arrangement of internal organs - E.M. Khoroshun; V.V. Makarov; V.V. Nehoduiko; S.A. Shypilov; S.V. Tertyshnyi; K.S. Slesarenko (Хірургія дитячого віку)
The aim is to demonstrate a clinical case of blast injury of the chest and spine against the background of a complete mirror image arrangement of internal organs.